2010
DOI: 10.3390/ijms11104149
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Based Therapy for Ulcerative Colitis—Modulation of Intestinal Mucus Membrane Phospholipids as a Tool to Influence Inflammation

Abstract: Ulcerative colitis (UC) is the result of an inappropriate colonic inflammatory response triggered by environmental and genetic factors. We have recently shown that mucus from UC patients has a decreased phosphatidylcholine (PC) content, while clinical trials revealed that therapeutic addition of PC to the colonic mucus alleviated the inflammatory activity. The mechanisms behind this are still unclear. We hypothesized that PC has at least two possible functions in the intestine: First, it establishes the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 73 publications
0
54
0
Order By: Relevance
“…Treede et al [136] and Taylor et al [36] explained the anti-inflammatory effects of PC with inhibition of TNF alpha and TNF beta , whose reduced levels might also play positive roles on weight control. In addition, PC administration improves colitis mostly because it restores the appropriate gastrointestinal concentrations of this PL, which decrease with inflammation [137][138][139][140]. PC also improves the effects of NSAIDs [141] and reduces their gastric side effects via PGE-mediated gastric juice production [142].…”
Section: Inflammation and Related Diseasesmentioning
confidence: 96%
“…Treede et al [136] and Taylor et al [36] explained the anti-inflammatory effects of PC with inhibition of TNF alpha and TNF beta , whose reduced levels might also play positive roles on weight control. In addition, PC administration improves colitis mostly because it restores the appropriate gastrointestinal concentrations of this PL, which decrease with inflammation [137][138][139][140]. PC also improves the effects of NSAIDs [141] and reduces their gastric side effects via PGE-mediated gastric juice production [142].…”
Section: Inflammation and Related Diseasesmentioning
confidence: 96%
“…The overall thickness of the adherent mucus layer in the colorectum is reduced due to overall depletion of goblet cells [115, 116], accompanied by reduced expression of the protective trefoil peptides [117]. Additionally, altered lipid composition [118, 119] may be responsible for the observed decrease in surface tension and hydrophobicity in clinical specimens obtained from UC patients [120]. Although it is not clear which factor contributes most to UC pathogenesis, it was recently found in a phase IIa/b studies that lipid supplementation in the colon led to mucosal healing in 60% of patients [121].…”
Section: Alterations To the Mucus Barrier In Disease Statesmentioning
confidence: 99%
“…In consistent with our previous studies, we found PC containing liposomes show good anti-inflammatory activities [6]. In the human intestinal epithelial cell line Caco-2, PC down-regulated TNF-α-induced gene expressions of pro-inflammatory cytokines such as ICAM-1, MCP-1, IL-8 and IP-10 through the inhibition of NFκB activation and hence lipid based therapy with PC may have benefits for ulcerative colitis, through anti-inflammatory effect [41,42]. Taken together, the behavior of osteoblasts under the stimuli of different liposomal formulations can be arranged in the following rank order PC liposomes > DC-Chol/DOPE liposomes > PC/DOTAP liposomes = Chol/DOTAP liposomes.…”
Section: Discussionmentioning
confidence: 99%